PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI DI SMA SWASTA SINGOSARI KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2025 - Marlina, Siti -; Tanjung, Tiara (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Adolescence is a transition period marked by physical, emotional, and psychological changes. During adolescence, girls will experience a natural process, namely menstruation. As an effort to maintain the health and cleanliness of reproductive organs, personal hygiene of genitalia is very necessary. Lack of knowledge in carrying out personal hygiene of genitalia can cause various diseases of the reproductive organs. Purpose: This study aims to determine the effect of health education on knowledge of personal hygiene during menstruation in female adolescents at Singosari Deli Tua Private High School. Method: This type of research is quantitative, with a pre-experimental method with one group pretest-protest design. The population in this study were girls who had menstruated at Singosari Deli Tua Private High School, a sample of 87 female students. After the data was collected, data processing was carried out through the stages of editing, coding, scoring, and tabulating. Data analysis used the Wilcoxon Sign Test to see the effect of health education on knowledge of personal hygiene during menstruation before and after education was given. The results of the study showed that knowledge before being given health education about personal hygiene during menstruation was well-informed by 44 respondents (50,6%), then after being given health education, 58 respondents (66.7%) had good knowledge. There was an influence of health education on knowledge of personal hygiene during menstruation in female adolescents at Singosari Deli Tua Private High School with the results of the Wilcoxon Sogn Test, the significance value of knowledge was 0.000 or p <0.05. Conclusion: Based on the results of this study, it is expected that female students will always maintain their feminine area by doing personal hygiene properly and correctly in accordance with the provisions of health workers, especially during menstruation.